Tourists perceptions of Caribbean islands facing environmental threats before the COVID-19 health crisis: Holbox Island and Archipelago of Bocas del Toro - Rubio Cisneros, Nadia T.; Ruiz Aymá, Gabriel; González Rojas, José Ignacio; Montero Muñoz, Jorge L.; Rubio Cisneros, Igor Ishi; Morales, Sara; Pech, Monica; Baker, Rachel; Jimenez, Armando; Fuentes, Karen (Plos one, 2022)
Data from the tourists´ surveys were analyzed by summing up the number of responses for each answer category of each survey question. All information was plotted into bar charts. To further explore the differences between the responses of tourists in Holbox and ABT.